Hubungan Antara Tingkat Kecerdasan Emosional dan Budaya Organisasi dengan Kepemimpinan Paedagogis Guru Penggerak Lintas Angkatan di Kabupaten Solok Sumatera Barat (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the influence of emotional intelligence and organisational culture on the pedagogical leadership of motivational teachers. The background of this study is based on findings of variations in emotional intelligence, resistance to change, and differences in school organisational culture that affect the effectiveness of motivational teachers' leadership in carrying out their role as agents of change. This study uses a quantitative approach with a population of 206 motivational teachers from the fourth, eighth, and ninth batches in Solok Regency. The research sample consisted of 67 respondents selected using stratified random sampling. Data were collected through a questionnaire that had been tested for validity and reliability, then analysed using classical assumption tests, simple linear regression, and multiple linear regression. The results showed that emotional intelligence had a positive and significant effect on the pedagogical leadership of motivational teachers by 70.1%, while organisational culture had a positive and significant effect by 65.4%. Simultaneously, emotional intelligence and organisational culture have a positive and significant influence on the pedagogical leadership of motivational teachers by 73.4%. These findings emphasise the importance of strengthening emotional aspects and organisational culture in improving the effectiveness of the pedagogical leadership of motivational teachers